Presença da cosmovisão religiosa na construção discursiva de mundo - Farias Francelino, Pedro; Brait, Beth; Cruz Pistori, Maria Helena; Lopes-Dugnani, Bruna; Stella, Paulo Rogério; Gontijo Rosa, Carlos (Bakhtiniana. Revista de Estudos do Discurso, 2023)
Editorial 19.1